Targeted control of supporting pathways in paclitaxel biosynthesis with CRISPR-guided methylation - Brzycki Newton, Cassandra; Young, Eric M.; Roberts, Susan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Plant cell culture biomanufacturing is rapidly becoming an effective strategy for production of high-value plant natural products, such as therapeutic proteins and small molecules, vaccine adjuvants, and nutraceuticals. Many of these plant natural products are synthesized from diverse molecular building blocks sourced from different metabolic pathways. Even so, engineering approaches for increasing plant natural product biosynthesis have typically focused on the core biosynthetic pathway rather than the supporting pathways. Methods: Here, we use both CRISPR-guided DNA methylation and chemical inhibitors to control flux through the phenylpropanoid pathway in Taxus chinensis, which contributes a phenylalanine derivative to the biosynthesis of paclitaxel (Taxol), a potent anticancer drug. To inhibit PAL, the first committed step in phenylpropanoid biosynthesis, we knocked down expression of PAL in Taxus chinensis plant cell cultures using a CRISPR-guided plant DNA methyltransferase (NtDRM). For chemical inhibition of downstream steps in the pathway, we treated Taxus chinensis plant cell cultures with piperonylic acid and caffeic acid, which inhibit the second and third committed steps in phenylpropanoid biosynthesis: cinnamate 4-hydroxylase (C4H) and 4-coumaroyl-CoA ligase (4CL), respectively. Results: Knockdown of PAL through CRISPR-guided DNA methylation resulted in a profound 25-fold increase in paclitaxel accumulation. Further, through the synergistic action of both chemical inhibitors and precursor feeding of exogenous phenylalanine, we achieve a 3.5-fold increase in paclitaxel biosynthesis and a similar reduction in production of total flavonoids and phenolics. We also observed perturbations to both activity and expression of PAL, illustrating the complex transcriptional co-regulation of these first three pathway steps. Discussion: These results highlight the importance of controlling the metabolic flux of supporting pathways in natural product biosynthesis and pioneers CRISPR-guided methylation as an effective method for metabolic engineering in plant cell cultures. Ultimately, this work demonstrates a powerful method for rewiring plant cell culture systems into next-generation chassis for production of societally valuable compounds.